Robotic-assisted thoracic surgery following neoadjuvant chemoimmunotherapy in patients with stage III non-small cell lung cancer: A real-world prospective cohort study - Gao, Yang; Jiang, Juan; Xiao, Desheng; Zhou, Yanwu; Chen, Yufan; Yang, Huaping; Wang, Lijing; Zeng, Jun; He, Baimei; He, Ruoxi; Li, Min; Liu, Zhaoqian (Frontiers in Oncology, 2022)
Objective: Stage Ⅲ non-small cell lung cancer (NSCLC) is a heterogeneous group of diseases. For this subset of patients, clinical management is still under debate and prognosis remains poor so far. In the present study, we aimed to evaluate the feasibility and safety of robotic-assisted thoracic surgery after neoadjuvant chemoimmunotherapy in stage Ⅲ NSCLC. Methods: A real-world prospective cohort study was performed in a single-center setting from April 2021 to May 2022. Patients who were diagnosed with resectable or potentially resectable stage ⅢA-B NSCLC and received neoadjuvant chemoimmunotherapy followed by robotic-assisted thoracic surgery were enrolled. Pathological response to neoadjuvant chemoimmunotherapy, treatment-related adverse events and surgical outcomes of these patients were evaluated. Results: A total of 44 patients who underwent robotic-assisted thoracic surgery after 3 doses of neoadjuvant chemoimmunotherapy were included in this study. Of these, 36 of 44 (81.8%) patients had major pathological response, and 26 (59.1%) had pathological complete response based on pathological examination of surgical specimen. Eight patients (18.2%) suffered grade 3 treatment related adverse events, including neutropenia (n=4), increased aminotransferases (n=3), anemia (n=1) and cutaneous capillary endothelial proliferation (n=1). Robotic-assisted thoracic surgery was performed subsequently, and R0 resection was achieved in all patients. Only 2 (4.5%) patient required conversion to thoracotomy. Surgical complications occurred to 5 (11.4%) patients, including air leak (n=3), chylothorax (n=2) and surgical site infection (n=1). There was no re-surgery or postoperative mortality within 90 days. Conclusion: Robotic-assisted thoracic surgery following neoadjuvant chemoimmunotherapy showed good feasibility and safety in stage Ⅲ NSCLC. It was not associated with unexpected perioperative morbidity or mortality, and may be a promising therapeutic option in stage Ⅲ NSCLC. These results need further confirmation by more large-scale clinical trials.